A community for students. Sign up today!
Here's the question you clicked on:
← 55 members online
 0 viewing

This Question is Closed

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.1(fog)(x) = f(g(x)) = f(x+1)

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.1@shivraj u got what I did??????

miteshchvm
 2 years ago
Best ResponseYou've already chosen the best response.0that means you need to put x= x + 1 in f(x)

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.1Yep: (fog)=f(g(x))

sauravshakya
 2 years ago
Best ResponseYou've already chosen the best response.1Now, substitute there g(x)

miteshchvm
 2 years ago
Best ResponseYou've already chosen the best response.0suppose f(1) = 0 f(x) = x^2  1 f[g(x)] = (x+1)^2  1

miteshchvm
 2 years ago
Best ResponseYou've already chosen the best response.0you got it? @shivraj

godfreysown
 2 years ago
Best ResponseYou've already chosen the best response.1if \[f(x)=x^21\ and \ g(x)=x+1, \\ \ then \ (fog)'(x)=\ (by \ product \ rule)\ u'v+u'v, \\where\ u=f(x); \ v=g(x) \\ \therefore\ (x^21)(1)+(2x)(x+1)=\\x^21+2x^2+2x=\\3x^2+2x1=\\(3x1)(x+1) \]
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.